To evaluate diagnostic efficacy of maternal serum C - reactive protein to predict preterm labour - Gahlot, Kavita; Pandey, Kiran; Singh, Punya P.; Gahlot, Vikash; Mourya, Rajesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Preterm birth is a major challenges faced by obstetricians worldwide. Globally, an estimated 13 million babies are born before 37 completed weeks of gestation annually. Preterm birth is the leading direct cause of neonatal death (27%); more than one million preterm newborns die annually. According to report ‘India is among the top 10 countries that account for 60 per cent of the world’s preterm births. Methods to detect preterm labour early include ultrasound examination of the cervix and detection of biochemical markers of preterm labour in blood (include serum C - reactive protein level) and cervicovaginal secretions. The objective of the study was evaluate diagnostic efficacy of maternal serum C - reactive protein (CRP) to predict preterm labour. Methods: A prospective study comprised of a total of 132 pregnant women with singleton fetus with symptoms of preterm labour. Serum CRP values was taken in all patients. Out of which 17 patients were lost during follow up, 3 patients develop PPROM. Hence study was conducted over 112 patients. Among these 62 patients went in preterm labour and 50 patients delivered at term. Results: For predicting preterm delivery sensitivity, specificity, positive and negative predictive value for serum CRP were 70.9%, 70%, 74.5% and 66% respectively. Conclusions: Serum CRP is good predictor to differentiate the women who were likely to deliver preterm. CRP positivity in early pregnancy is associated with nearly a twofold increased risk of preterm delivery.